Two new Nolini (Lepidoptera: Nolidae: Nolinae) from Nouabalé-Ndoki National Park, Republic of Congo - László, Gyula M. (Zootaxa, 2023)
A new species of Bellanola László, 2022 (B. ndoki László, sp. n.) and a new species of Meganola Dyar, 1898 (M. faber László, sp. n.) are described and figured from the Nouabalé-Ndoki National Park, Republic of Congo. The former new species is the second known taxon of the recently described genus Bellanola, whilst the latter is attributed to the Meganola chionea (Hampson, 1911) species-group. The paper is illustrated with habitat photographs and eight colour and eight black and white images of diagnostic features.